Integrasi Pemikiran Rekonstruksionisme dalam Pendidikan Agama Islam: Analisis Kritis Systematic Literature Review - Tetambe, Ahmad Ghifari; Bahri, Samsul; Musthan, Zulkifli; Shaleh, Muh. (Jurnal Pendidikan Agama Islam Al-Thariqah, 2025)
This article aims to analyse the integration of reconstructionist thought in Islamic Religious Education. Reconstructionism as an approach in educational philosophy views education as an important instrument in the process of social change. In the realm of contemporary Islamic education, this approach has become a strategic alternative in responding to the challenges of modernity, the crisis of values, and the need for curriculum reform. This study adopts the Systematic Literature Review (SLR) method to examine five scientific articles highlighting the application of reconstructionist thought in the context of Islamic education. The research findings indicate that reconstructionist principles play a significant role in strengthening character education, redesigning the curriculum, mainstreaming the Islamization of knowledge, and fostering social awareness among students. The results of this study provide a solid theoretical foundation for the development of a more progressive, adaptive, and contextual model of Islamic education